Deep Integration and Trade: UK Firms in the Wake of Brexit - Rebecca Freeman; Marco Garofalo; Enrico Longoni; Kalina Manova; Rebecca Mari; Thomas Prayer; Thomas Sampson (CESifo GmbH, 2025)
How does dismantling deep integration affect international trade? This paper provides new evidence on the consequences of disintegration by estimating the impact of Brexit on goods trade by UK firms. The UK's exit from the EU's single market and customs union in January 2021 led to an immediate, sharp drop in both exports and imports with the EU for the average firm. In addition, many exporters and importers stopped trading with the EU entirely. However, heterogeneous firm-level responses to the implementation of trade barriers mitigated Brexit's impact on aggregate trade. The decline in exports was concentrated among smaller firms, but insignificant for the largest firms. Our estimates imply that, in the short run, leaving the EU reduced worldwide UK exports by 6:4% and worldwide imports by 3:1%. The fall in imports was driven by lower imports from the EU, which importers offset by sourcing more from the rest of the world.
Keywords: F13; F14; F15; 330; trade policy; Brexit; disintegration; deep integration